2016
DOI: 10.1177/0093650216631096
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Some Intercultural Negotiations More Difficult Than Others? Power Distance and Culture-Role Combinations

Abstract: This study examines whether and how intercultural negotiation dyads that vary in culture-role combinations experience different negotiation processes and outcomes. Participants completed an employment contract negotiation with a culturally different counterpart. Results indicated that high-status, high-power distance negotiators paired with low-status, low-power distance negotiators experienced more anger, placed less emphasis on cooperative goals, used less priority information exchange, and, consequently, ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…Clear, unimpeded communication is challenging in cross‐cultural negotiation, where negotiators typically have distinct negotiation schemas (Adair, Taylor, & Tinsley, ; Liu et al., ) and scripts (Adair et al., ; Brett & Okumura, ; Liu, ), that can result in misunderstanding. Communication quality differences in inter‐ and intracultural negotiation suggest that accurately communicating needs and intentions is more challenging in intercultural negotiations (Liu, Chua, & Stahl, ; Liu, Zhu, & Cionea, ). In part, the challenge occurs, as in the opening example, because norms governing politeness and other aspects of communication put negotiators from different cultures at risk of violating their counterparts’ expectations about social interactions.…”
Section: Communication Processesmentioning
confidence: 99%
“…Clear, unimpeded communication is challenging in cross‐cultural negotiation, where negotiators typically have distinct negotiation schemas (Adair, Taylor, & Tinsley, ; Liu et al., ) and scripts (Adair et al., ; Brett & Okumura, ; Liu, ), that can result in misunderstanding. Communication quality differences in inter‐ and intracultural negotiation suggest that accurately communicating needs and intentions is more challenging in intercultural negotiations (Liu, Chua, & Stahl, ; Liu, Zhu, & Cionea, ). In part, the challenge occurs, as in the opening example, because norms governing politeness and other aspects of communication put negotiators from different cultures at risk of violating their counterparts’ expectations about social interactions.…”
Section: Communication Processesmentioning
confidence: 99%
“…To control for extraneous factors that may generate power difference, such as BATNAs, participants in 1 The intracultural data were used by Liu (2009) to examine cultural variations in the effect of anger on negotiation performance and were used by Liu and Wilson (2011) to assess how interaction goals influenced individual and joint gains through dyad members' bargaining tactics. The intercultural data were used by Liu et al (2016) to examine whether dyadic composition of intercultural dyads affected negotiators' emotions, goals, bargaining tactics, and negotiation outcomes. The current study for the first time (a) compared intercultural and intracultural negotiations, and (b) examined the effects of power distance on bargaining tactics in negotiations that involve status-based distinguishable roles.…”
Section: Experimental Design and Hypothetical Scenariosmentioning
confidence: 99%
“…For example, Liu et al. () found that when negotiating inter‐culturally, negotiators vary significantly in their emotions, goal pursuit, and bargaining strategies depending on dyadic role composition, suggesting that intercultural negotiations can be more effective when dyad members’ culture‐role combinations are more conducive to empathy and perspective taking.…”
mentioning
confidence: 99%
See 2 more Smart Citations